Complete larval development of the hermit crabs Clibanarius aequabilis and Clibanarius erythropus (Decapoda : Anomura : Diogenidae), under laboratory conditions, with a revision of the larval features of genus Clibanarius - Bartilotti, Catia (2008)
The complete larval development (four zoeae and one megalopa) of Clibanarius aequabilis and C. erythropus, reared under laboratory conditions, is described and illustrated. The larval stages of the two northeastern Atlantic Clibanarius species cannot be easily differentiated. Their morphological characters are compared with those of other known Clibanarius larvae. The genus Clibanarius is very homogeneous with respect to larval characters. All Clibanarius zoeae display a broad and blunt rostrum, smooth abdominal segments and an antennal scale without a terminal spine. Beyond the second zoeal stage, the fourth telson process is present as a fused spine, and the uropods are biramous. In the fourth larval stage all species display a mandibular palp. The Clibanarius megalopa presents weakly developed or no ocular scales, symmetrical chelipeds, apically curved corneous dactylus in the second and third pereiopods, and 5-11 setae on the posterior margin of the telson. Apart from the number of zoeal stages, Clibanarius species may be separated, beyond the second zoeal stage, by the telson formula and the morphology of the fourth telson process.